Two species of swimming crabs of the genus Achelous (Crustacea, Brachyura): environmental requirements determining the niche - Lima, P. A. [UNESP]; Andrade, L. S. [UNESP]; Alencar, C. E. R. D.; Pereira, R. T. [UNESP]; Teixeira, G. M.; Fransozo, A. [UNESP] (Springer, 2014)
The overlap of niches of the swimming crabs Achelous spinicarpus and A. spinimanus on the southeastern coast of Brazil was investigated through biological and environmental samplings made monthly during 1 year, covering depths from 5 to 40 m. The abundance of the temporal bathymetric distributions was analyzed by a generalized linear model. A principal components analysis determined the environmental factors that explained most of the data variation, and then one redundancy analysis assessed the influence of these variations on the species' abundance. A. spinicarpus was most abundant during the summer and at greater depths, while individuals of A. spinimanus were collected in larger numbers during the winter and spring, at 25 m. The abundance of A. spinicarpus was positively correlated with depth and with the influence of the intrusion of the South Atlantic Central Water (SACW), whereas A. spinimanus was positively correlated with the organic-matter content in the sediment. A. spinicarpus can be considered an indicator of cooler waters, because it is abundant in regions and periods that are directly influenced by the SACW. The niches of these congeners do not overlap, and appear to be determined mainly by the environmental requirements of each species.
Keywords: Coexistence; Ecological distribution; Portunidae; Portunus; South Atlantic Central Water